Mathematical model for identifying and quantifying the overall environmental cost - Capusneanu, Sorinel; Topor, Dan Ioan; Stefan Hint, Mihaela; Ionescu, Constantin Aurelian; Coman, Mihaela Denisa; Paschia, Liliana; Gudanescu Nicolau, Nicoleta Luminita; Ivan, Oana Raluca (Journal of Business Economics and Management, 2020)
The paper deals with the environmental costs (EC) in the electrical equipment industry by using environmental accounting as a strategic instrument for controlling the economic entity (EE). The novelty of the study consists of integrating a mathematical model in environmental management accounting (EMA), starting from the identification of the types of waste generated by the production flow and the interaction between the production activity and the environment, which results in determining the EC per entity. The research also analyzes the dependence between the resulting waste and the volume of production by categories. The usefulness of determining these dependencies leads to the identification of the product categories with a significant influence on the EC. The study is useful for developing an environmentally sustainable accounting system within entities in the electrical equipment industry because based on the mathematical model, products that generate large quantities of waste can be identified, allowing the outline of managerial strategies to reviewing production technologies, in order to optimize the products and reduce the quantities of waste generated.